A comparative study on RIPASA and modified Alvarado score in the diagnosis of acute appendicitis in tertiary care hospital - Rao, Kodenge Raghavendra; Harika, D. Navya Sesha; Narayana, Suragani V.; K. S., Vinodh Kumar; Kumar Yadav, Chavala Pavan; Usha Kiran, Samireddi Harshita; Pavani, Namburi (International Surgery Journal, 2021)
Background: Acute Appendicitis is common surgical emergencies with a lifetime prevalence of approximately 1 in 7. Despite advances in diagnosis and treatment; acute Appendicitis is still associated with morbidity (10%) and mortality (1-5 %). Presentations of acute Appendicitis can mimic various acute medical and surgical conditions, and the diagnosis is predominantly a clinical one-different scoring systems used for aiding in early diagnosis of Acute Appendicitis and its prompt management. Alvarado score and RIPASA score are the most popular ones. So we retrospectively applied and compared Alvarado and RIPASA score in the diagnosis of acute Appendicitis in Indian population. Methods: In this study, we compared RIPASA score and Alvarado scoring system retrospectively by applying to 74 patients. This study period from November 2018 to March 2020. Both scores were calculated for patients presented with right iliac fossa pain. Sensitivity, specificity, positive predictive value (PPV), negative predictive (NPV), diagnostic accuracy for RIPASA and Alvarado system was calculated. Results: The sensitivity and specificity of the Alvarado score were 85.07% and 57.14% respectively. The sensitivity & specificity of RIPASA score were 91.04% and 71.42% respectively. Accuracy of the Alvarado scoring system is 82.44% and for RIPASA scoring system is 89.18%. The results show that the RIPASA scoring system is a better diagnostic tool for the diagnosis of Acute Appendicitis. Conclusions: RIPASA scoring system is simple, accurate, convenient, and more specific scoring system than the modified Alvarado scoring system for the Indian population.